The pelvic floor support in operative hysteroscopy patients (Annals of Medical Research, 2021)
Aim: Pelvic organ prolapse is a pelvic floor disorder in which advancing age, obesity, and parity are the main risk factors. Although it is known that the prevalence is around 10% in the whole population, approximately half of the cases are asymptomatic. Pelvic organ prolapse is not expected in the absence of risk factors such as obesity, age, and parity. The aim of this study was to evaluate the pelvic floor support -without these risk factors- in patients who underwent operative hysteroscopy for benign gynecological reasons in a university hospital.Material and Methods: In this prospective study, the Pelvic Organ Prolapse Quantification System (POP-Q) examination was performed in patients undergoing operative hysteroscopy with benign gynecological indications. The relationship between pelvic organ prolapse and risk factors such as obesity, age, and parity was investigated in these patients who were asymptomatic for pelvic floor disorders.Results: 1256 patients underwent operative hysteroscopy under general anesthesia with benign gynecological indications. The mean age of the patients was 29.8 years. The most common indication for operative hysteroscopy was the endometrial polyps (21.9%). None of the patients who underwent operative hysteroscopy had any symptoms of pelvic floor disorders. Pelvic organ prolapse was detected in 57.5% of the patients in Stage-0, 22.4% in Stage-1, 19.2% in Stage-2, and 0.9% in Stage-3. None of the patients had total uterine procidentia (Stage-4). Even though they were asymptomatic, stage-2 pelvic organ prolapse was detected in 20% of normal-weight nulliparous patients younger than 30 years.Conclusion: Pelvic floor disorders can also be seen in non-obese and nulliparous patients at a young age. Although such patients are asymptomatic, they should be referred to urogynecology clinics for optimal pelvic floor support in the following years.Keywords: Operative hysteroscopy; pelvic organ prolapse; pelvic floor
Keywords: Operative hysteroscopy; pelvic organ prolapse; pelvic floor